Prospective Evaluation of Patients Undergoing Translabyrinthine Excision of Vestibular Schwannoma with Concurrent Cochlear Implantation. Issue 10 (December 2017) - Rooth, Meredith A.; Dillon, Margaret T.; Brown, Kevin D.
Abstract : Objective: Translabyrinthine (TL) vestibular schwannoma (VS) resection may be accomplished with preservation of the cochlear nerve, permitting successful, concurrent cochlear implantation. In this single institution, Food and Drug Administration-approved feasibility study, we wished to determine the success and outcomes of concurrent cochlear implantation at the time of TL resection of VS. Study Design: Prospective cohort. Setting: Tertiary referral center. Patients: Patients with small VS less than 1.5 cm in size. Intervention: Concurrent TL VS resection and cochlear implantation. Main Outcome Measure: Sound localization and speech understanding. Results: All cochlear nerves were anatomically preserved. Five out of seven patients had auditory precepts at the time of activation. At 1 month following surgery, AzBio scores (0 dB SNR, with sound front, noise to normal ear) were improved by an average of 10% with implant on, persisting to 6 months out from surgery. Localization 1 month after surgery was markedly improved with root mean square 78 degrees ±13 in the "implant off" condition and 41 ± 9 degrees in the "implant on" condition. Average tinnitus severity was reduced in subjects and speech and spatial hearing was improved on speech, spatial and qualities of hearing scale (SSQ). Conclusions: These data demonstrate preservation of electrical hearing in TL VS surgery is consistently possible, and although speech outcomes do not achieve the same levels seen with other etiologies of hearing loss, excellent improvement in sound localization, improved speech understanding, and substantial reductions in tinnitus are achieved.